THE IMPACT OF ARTIFICIAL INTELLIGENCE TECHNOLOGY ON THE FUTURE OF COMMUNICATION - Harjono Padmono Putro (BIOS: Jurnal Informatika dan Sains, 2023)
Artificial intelligence has become an integral component in the development of information and communications technology, influencing human interactions on a significant scale. This research aims to investigate the impact of the use of artificial intelligence (AI) on various aspects of communication in various contexts. This research uses a qualitative approach with descriptive methods. The research results show that the application of artificial intelligence in communications, such as virtual assistants, chatbots, and AI translation tools, has brought about significant changes in the ease and effectiveness of human interaction. In a business context, the use of artificial intelligence to personalize communications has increased customer engagement, satisfaction and reduced churn rates. Apart from that, AI has also opened up more inclusive communication access for people with disabilities through text-to-speech and speak-to-text technology. Even though the results are positive, it is important to remember that challenges related to ethics, privacy and data security are still major concerns in implementing this technology. With wise understanding, the development of artificial intelligence in the field of communications can provide sustainable benefits for society.